Design and Development of Hyaluronic Acid Surface Modified Astaxanthin Loaded Chitosan Nanoparticles for Enhanced Anti-Tumour Efficacy in Hepg2 Cells (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Astaxanthin is a marine-derived carotenoid with potent antioxidant and anticancer properties. However, its therapeutic application is restricted by poor aqueous solubility, instability, and low bioavailability. This study aimed to develop hyaluronic acid (HA) surface-modified astaxanthin-loaded chitosan nanoparticles to enhance targeted anticancer efficacy against HepG2 liver cancer cells. The objectives included formulation, physicochemical characterization, compatibility assessment, in vitro drug release, and cytotoxicity evaluation. Nanoparticles were prepared by molecular self-assembling and high-pressure homogenizing. The formulations were characterized for particle size, polydispersity index (PDI), zeta potential, morphology, drug loading, and entrapment efficiency. FTIR and DSC analyses were performed to evaluate drug-polymer compatibility. Drug release and MTT assay with HepG2 cells were conducted to evaluate drug release and anticancer activity. The optimized formulation (F1) had a particle size of 110.6 nm, PDI of 0.282 and Zeta potential of +32 mV. FTIR and DSC showed successful physical encapsulation without drug-polymer interaction. The optimized nanoparticles released 95.14% of the drug in comparison to 25.18% for free astaxanthin and exhibited greater toxicity towards HepG2 cells. HA surface modified astaxanthin loaded chitosan nanoparticles had remarkable properties of drug release, stability and in vitro anticancer activity which have potential to use as a targeted nanocarrier for the treatment of hepatocellular carcinoma.
Keywords: Astaxanthin; Chitosan; Nanoparticles